Computer‐Aided Design, Synthesis and Validation of 2‐Phenylquinazolinone Fragments as CDK9 Inhibitors with Anti‐HIV‐1 Tat‐Mediated Transcription Activity. Issue 12 (21st October 2013) - Sancineto, Luca; Iraci, Nunzio; Massari, Serena; Attanasio, Vanessa; Corazza, Gianmarco; Barreca, Maria Letizia; Sabatini, Stefano; Manfroni, Giuseppe; Avanzi, Nilla Roberta; Cecchetti, Violetta; Pannecouque, Christophe; Marcello, Alessandro; et al.
Abstract The activity of the cyclin‐dependent kinase 9 (CDK9) is critical for HIV‐1 Tat‐mediated transcription and represents a promising target for antiviral therapy. Here we present computational studies that, along with preliminary synthetic efforts, allowed us to identify and characterize a new class of nontoxic anti‐CDK9 chemotypes based on the 2‐phenylquinazolinone scaffold. Inhibition of CDK9 translated into the ability to interfere selectively with Tat‐mediated transactivation of the viral promoter and in the inhibition of HIV‐1 reactivation from latently infected cells, with the most potent derivative 37 (2‐(4‐aminophenyl)‐7‐chloroquinazolin‐4(3H)‐one) showing an IC50 value of 4.0 μM. Because the herein reported 2‐phenylquinazolinones are merely fragments, they are largely optimizable, paving the way to derivatives with improved potency.